ANALISA KEGAGALAN PLATEN TUBE SUPERHEATER PLTU TELUK SIRIH - Redaksi Tim Jurnal (JURNAL POWERPLANT, 2018)
Superheater is a main part of boiler that serves as one of steam temperature riser after water evaporated by heat inside a boiler. The steam comes out from boiler drum, by utilizing hot air flowinside boiler. Superheater tube is a very important part of process inside the plant, with a high operating temperature of 540°C (in PLTU Teluk Sirih). Because of this, the tube will be maintained by inspection on each scheduled shutdown. Leakages often occur in platen tube of superheater, exactly at its bend or elbow tube. To know causes of the leakages of the part, we conducted observation analysis i.e., visual observation (metallographic testing), spectrometry and hardness test. From the metallographic test analysis, pearlite and ferrite phases present. At the leakage part, it could be observed the tube has lost much of pearlite phase caused by heating. Pearlite micro structure indicates hardness of a material. In spectrometry test of the leaked tube sample using ASTM SA213 T22 standard, value of carbon rises very high by 0.148 from normal value, 0.15 at maximum. We also obtained from it average hardness of 178 HB (ASTM standard). From analysis of the superheater platen tube, damage caused by abrasion of bad materials hit the tube and decreasing pearlite phase caused by temperature changes. Tiny parts of the tube that hit by steam fell eroded and over time the tube broken. Another thing we can conclude is burst of fire in boiler may cause thinning and tube leakage.